Violation of the Cooperative Principle by Characters in the Knives Out Movie - Dewi, Eli Marta; Pradipta, Bramantya (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
Abstract. This study investigates how characters in the Knives Out movie violate Grice’s Cooperative Principle, which consists of four conversational maxims: Quantity, Quality, Relation, and Manner. The objective of this study is to identify the types of maxim violations that occur, determine which maxim is most frequently violated, and analyze the effects of each violation on character interaction and interpretation of meaning. The study uses a descriptive qualitative method within the field of pragmatics, focusing on how maxim violations appear naturally in the characters’ utterances without altering the original dialogue. The data were collected from selected utterances in the Knives Out movie and analyzed using Grice’s (1975) theory of the Cooperative Principle. The findings reveal a total of 52 maxim violations, consisting of 22 violations of the Maxim of Quality, 13 of Quantity, 11 of Manner, and 6 of Relation. The Maxim of Quality is the most frequently violated, reflecting how deception and false information play a central role in shaping the mystery and building tension in the movie. Each maxim violation contributes differently to the narrative. Violations of Quality often involve lies or misleading statements; Quantity violations are used to withhold important information; Relation violations serve to redirect conversations; and Manner violations introduce ambiguity. These strategic violations affect how characters interact, how information is interpreted, and how the plot unfolds. This study contributes to a deeper understanding of how conversational principles are manipulated in fictional narratives, especially in the mystery genre. Keywords : Cooperative Principle, Knives Out, Maxim Violation, Pragmatics